Increased vascularization of the subchondral region in human osteoarthritic femoral head in the elderly - Yuqi He; Katrin Bundkirchen; Shahed Taheri; Ricarda Stauß; Emmanouil Liodakis; Claudia Neunaber; Arndt F. Schilling; Christian Mühlfeld; Stephan Sehmisch; Tilman Graulich (Histochemistry and Cell Biology, 2025)
This study aimed to quantitatively analyze subchondral vascularization during the progression of osteoarthritis (OA) in the elderly, particularly regarding the timing of initial blood vessel emergence and when their density peaks. A total of 129 independent areas from 43 human femoral heads, obtained through arthroplasty for OA or hemiarthroplasty for fractures, were analyzed. The femoral heads were grouped by Kellgren-Lawrence (KL) grades: KL 1 (6 heads), KL 2 (14 heads), KL 3 (10 heads), and KL 4 (13 heads), and the Mankin score was assessed. Quantitative measurements of blood vessel length 1 mm below the tidemark, cartilage volume and thickness, chondrocyte volume, ECM volume, subchondral bone volume, and bone marrow volume were performed using stereology and immunohistochemistry. The most substantial increase in the characteristics of blood vessels within the subchondral region began at KL 3 and peaked at KL 4. Blood vessel volume increased from 6.71 ± 5.84 mm 3 in group KL 1 to 156.21 ± 138.67 mm 3 in group KL 4 ( p < 0.001). Blood vessel surface area showed an increase from 14.78 ± 9.89 cm 2 (group KL 1) to 125.20 ± 93.18 cm 2 (group KL 4) ( p < 0.001). Likewise, blood vessel length grew from 27.53 m (IQR 13.70–65.41 m) in group KL 1 to 112.03 ± 76.07 m in group KL 4 ( p = 0.001). This study offers deeper insights into the role of vascularization in OA pathophysiology, quantifying subchondral blood vessel characteristics in the femoral head across different OA stages.